2013
DOI: 10.1177/0974929214538363
|View full text |Cite|
|
Sign up to set email alerts
|

Do Foreign Trade and Investment Lead to Higher CO2 Emissions? Evidence from Cross-Country Empirical Estimates

Abstract: The waves of globalisation in the past decades have increased the cross-country trade and investment flows, which also raise serious concerns over environmental sustainability and climate change owing to the following three effects. First, through scale effect the growing output and exports of the polluting sectors may adversely influence environmental balance. Secondly, growing trade volume can lead to change in industry structure and output composition resulting from composition effect, which may or may not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…From the perspective of curvilinearity and distribution lag, the carbon reduction effects of FDI inflows do not appear immediately. Specifically, FDI inflows are apparently not initially helpful for environmental improvement, but after 6 years, they do alleviate environmental pollution (Chakraborty & Mukherjee, 2013). From the perspective of heterogeneity, it has been found that the relationship between FDI and carbon emissions varies with different situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of curvilinearity and distribution lag, the carbon reduction effects of FDI inflows do not appear immediately. Specifically, FDI inflows are apparently not initially helpful for environmental improvement, but after 6 years, they do alleviate environmental pollution (Chakraborty & Mukherjee, 2013). From the perspective of heterogeneity, it has been found that the relationship between FDI and carbon emissions varies with different situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the existing theoretical and empirical literature explains the climate change related repercussions of international trade flows with help of three effects [24][25][26]. First, through scale effect the growing output and exports of the polluting sectors may adversely influence environment, as that may cause additional energy use and exploitation of natural resources [27].…”
Section: Economics Research Internationalmentioning
confidence: 99%